A Sensitive Solid-Phase Immunosorbent Assay for Tissue-Type Plasminogen Activator Activity in Plasma Using Trinitrobenzoylated Poly-D-Lysine as a Stimulator for Plasminogen Activation - Petersen, Lars Christian; Handest, Peter; Brender, Jytte; Selmer, Johan; Jørgensen, Maja; Thorsen, Sixtus (Thrombosis and Haemostasis, 1987)
A sensitive, specific and precise immunosorbent assay for tissue-type plasminogen activator (t-PA) activity in plasma was developed. It measured the single-chain and the two-chain forms of t-PA with equal sensitivity. The assay involved (I) coating of wells in microtiter plates with a monoclonal antibody directed towards an epitope on t-PA apart from the catalytic active site, (II) binding of t-PA to the solid-phase antibody, (III) activation of plasminogen by antibody-bound t-PA in the presence of a new potent stimulator, trinitrobenzyl alkylated poly-D-lysine (TNB-poly-D-Lysine) and measurement of plasmin activity with D-Val-Leu-Lys-pNA. Plasma samples were acid-treated and diluted 80 times in order to minimize the inhibitory effect of plasma on the assays. The assay could be performed within one working day with precoated microtiter plates.The sensitivity of the assay for t-PA in plasma was 1 pM (~70 ng/1). The recoveries of single-chain and two-chain t-PA added to plasma was 97-104%. The intraassay coefficient of variation was 3.4-5.1% and the interassay coefficient of variation was 7.8-18%. Resting values of t-PA in plasma for 42 healthy subjects ranged between 0 and 30 pM (median: 4.1 pM). The values after 10 min venous occlusion ranged between 1.2 and 520 pM (median: 100 pM). The t-PA concentrations determined by the immunosorbent assay correlated well with euglobulin clot lysis time measurements (r = 0.940).
Keywords: Assay; Monoclonal antibody; Plasma; Tissue-type plasminogen activator; Trinitrobenzoylated poly-D-lysine